Effect of Sun-Drying and Oven-Drying Processing Methods on the Chemical Composition of Bitter Leaves (Vernonia amygdalina) - Udoh, Mary Athanasius; Ijezie, Augustina Elochukwu; Abah, Scholastica Ene; Olayemi, Abimbola Gbenga; Yahaya, Musbau Adekunle; Mohammed, Kulu Sanda (Darul Yasin Al Sys, 2025)
Leafy vegetables, commonly consumed as edible plant shoots, are rich sources of macro- and micronutrients. Vernonia amygdalina (bitter leaves) is a widely consumed vegetable in Nigeria, especially among the Igbo community, where drying—either by sun or oven—is a prevalent preservation method that also enhances taste. This study investigates the effects of sun-drying and oven-drying on the chemical composition of Vernonia amygdalina leaves. Approximately 2.5 kg of fresh leaves were purchased from Watt Market, Calabar (South-South Nigeria), destalked, and divided into three equal portions. One portion was used as a control (fresh, unprocessed), while the other two were subjected to one-month drying treatments—sun-drying and oven-drying—before being pulverized into flours, sealed in airtight containers, and stored under cool, dry conditions. Standard analytical procedures were employed to assess proximate composition, elemental content, and phytochemical properties. Results revealed that both drying methods significantly reduced moisture content, leading to an increase in dry matter. Notably, the sun-dried samples showed increased ash (6.32 ± 0.02% vs. 2.45 ± 0.02% in control) and crude protein (6.23 ± 0.02% vs. 5.40 ± 0.1%), while oven-dried samples exhibited elevated crude fat (3.33 ± 0.2%), crude fibre (14.30 ± 0.1%), and carbohydrate content (52.10 ± 0.01%) compared to the control. Conversely, drying led to reductions in vitamin levels, mineral content, antinutrients, and food toxicants. These findings indicate that drying improves the nutritional density of macronutrients while decreasing potentially harmful components, thus enhancing the digestibility and safety of the leaves. The study concludes that sun and oven-drying are effective preservation techniques that significantly influence the nutritional profile of Vernonia amygdalina, with important implications for food security and dietary quality.